2009
DOI: 10.1111/j.1540-8167.2008.01355.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Catheter Forces, Lesion Characteristics, “Popping,” and Char Formation: Experience with Robotic Navigation System

Abstract: When using an OIC, lower power settings (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
100
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(103 citation statements)
references
References 22 publications
(20 reference statements)
0
100
1
2
Order By: Relevance
“…636,665,666,667 No effective lesion is formed without adequate CF, and excessive CF is associated with excessive deep tissue heating and an increased risk of deep steam pop (and perforation) and injury outside the heart, such as esophageal, pulmonary, and PN injury.…”
Section: Section 6: Technology and Toolsmentioning
confidence: 99%
“…636,665,666,667 No effective lesion is formed without adequate CF, and excessive CF is associated with excessive deep tissue heating and an increased risk of deep steam pop (and perforation) and injury outside the heart, such as esophageal, pulmonary, and PN injury.…”
Section: Section 6: Technology and Toolsmentioning
confidence: 99%
“…In contrast, excessively high CFs have been shown in animal models to be associated with steam pop and crater formation, and consciously avoiding such high forces with CF visualisation may reduce complication rates. 32 Impedance values during mapping and impedance drop that occurs at the start of RF application was also shown to correlate with CF, which has since been confirmed in a recent publication by Reichlin et al 33 Secondly, comparison of CF guided with non-CF guided LA mapping and PVI ablation was performed, and the impact of CF on AF recurrence was analysed. A total of 70 patients underwent PVI, in which operators were blinded to CF data in 35 patients, and CF was displayed in the other 35.…”
Section: The Impact Of Contact Forcementioning
confidence: 96%
“…Recent studies demonstrated that not only the power setting, but also the contact force of the cathetertip is an important factor to predict tissue temperature, lesion depth, popping, and crater formation experimentally. [14][15][16] In the previous experiments, a 30W constant power and mean RF delivery duration of 105 ± 17 seconds resulted in a mean maximum catheter-tip temperature of 42 ± 5°C, mean lesion volume of 514 ± 104 mm 3 , and mean lesion depth of 8.2 ± 1.2 mm. We observed popping in 1 out of 6 cooled-ablations.…”
Section: Discussionmentioning
confidence: 99%
“…The contact force of the catheter-tip also affects steam pop and thrombus formation in an open-irrigated ablation, therefore contact force also should be measured. [14][15][16] Conclusion: Temperature-controlled cooled-tip RFCA is feasible without "steam pop" and an abrupt rise in impedance using an RF generator that slowly increases the power to reach the preselected catheter-tip temperature.…”
Section: Discussionmentioning
confidence: 99%